2022
DOI: 10.1002/capr.12514
|View full text |Cite
|
Sign up to set email alerts
|

Pluralistic counselling versus counselling as usual for young people presenting with addiction issues: A pilot randomised controlled trial

Abstract: Aim The purpose of this study was to pilot a randomised controlled trial that aimed to test the hypothesis that counselling utilising a pluralistic framework was more effective than counselling as usual for young people experiencing issues as a result of their addiction. Method Sixty‐four clients presenting with issues of addiction were allocated to either a counselling‐as‐usual (n = 33) or a pluralistic (n = 31) intervention. Psychometric measures (YP‐CORE and SDQ) were taken at baseline, endpoint and 3‐month… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 43 publications
0
1
0
Order By: Relevance
“…Further, a lack of control and agency has been noted as an important factor in adults unilaterally discontinuing their psychiatric medications (Keogh et al, 2021) and the lack of involvement in medication decisionmaking has been found to be a challenge for young people with a mental illness (McMillan et al, 2020). More generally, favourable outcomes for collaborative models involving shared decision-making have also been found for pluralistic models of counselling for young people with substance use (Joyce et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Further, a lack of control and agency has been noted as an important factor in adults unilaterally discontinuing their psychiatric medications (Keogh et al, 2021) and the lack of involvement in medication decisionmaking has been found to be a challenge for young people with a mental illness (McMillan et al, 2020). More generally, favourable outcomes for collaborative models involving shared decision-making have also been found for pluralistic models of counselling for young people with substance use (Joyce et al, 2022).…”
Section: Discussionmentioning
confidence: 99%